Socialization of The Effectiveness Test of Antifungi Formulation of Garlic (Allium Sativum L.) Ethanol Extract Mouth on The Growth of Candida Albicans - Pranata, Chandra; Darmirani, Yosi; Pratiwi, Asti; Sumitra, Jhoti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Garlic plants (Allium sativum L.) can be found in almost all parts of Indonesia, including in Lubuk Pakam, Deli Serdang. The content contained in the ethanol extract of garlic has various secondary metabolites with a role as an antifungal, namely tannins, saponins, flavonoids, and alkaloids. As utilization and information to the public that garlic ethanol extract is made into mouthwash formulations. This article reports on outreach activities to the people of Lubuk Pakam, to be precise in Lubuk Pakam Pekan sub-district about the potential use of natural garlic mouthwash formulations. Testing the antifungal activity of mouthwash preparations was produced by showing the average diameter of inhibition in the form of F1 (12.3 mm), F2 (17.3 mm), F3 (18.5 mm) and F4 (21.6 mm). This means that the higher the concentration, the better the inhibition of garlic ethanol extract in inhibiting fungal growth.